PREDICTING EMPLOYEES' JOB SATISFACTION WITH PEOPLE-RELATED TQM PRACTICES: CASE IN APPAREL MANUFACTURING INDUSTRY, SRI LANKA - Chathurika, H.J.; Dileepa, M.E.W. (University of Jaffna, 2016)
People-Related Total Quality Management (PRTQM) practices mainly involve with the "soft" performance of the organization as same as human resource practices. Therefore, the PRTQM practices have a direct impact on employee satisfaction. Job satisfaction is identified as the main construct which effects on employees' commitment level, which leads to the productivity of the human resource. This paper focuses on to identify the relationship between the PRTQM practices and employees' Job Satisfaction in the context of the Apparel Manufacturing sector in Western Province in Sri Lanka. Senior level managers who belong to the areas of Production and Quality of 15 randomly selected Apparel Manufacturing organizations were used as the sample and a self-administered questionnaire was used to collect data. Psychometric evaluation of the measuring tool was done through Confirmatory Factor Analysis and Reliability Analysis. The Correlation Analysis was used to measure the strength and the significance of the relationship between the level of PRTQM practices and employees' Job Satisfaction. Multiple Linear Regression Analysis was used to measure the impact of individual PRTQM factors on the Job Satisfaction of senior Managers. Results of this study illustrated a positive relationship between PRTQM practices and employees' Job Satisfaction. The average level of Job Satisfaction and identification of the opportunities for Teamwork are significantly higher in females than their male counterparts. Compensation has no significant impact on Satisfaction. The level of influences of Leadership, Training opportunities, Empowerment, and Involvement, on the Job Satisfaction, varied according to the gender of the employee. Opportunities for Teamwork, Leadership, and Involvement are the significant factors for the Job Satisfaction of male employees but the Involvement and the Empowerment are the significant factors for the female employees. Ignoring the gender difference of the senior managers, Involvement, Leadership, and opportunities for Teamwork, together shows significant impact (R2= .381) on the Job Satisfaction of employees in the Apparel Manufacturing sector.
Keywords: People-related TQM; Employees' job satisfaction; Apparel manufacturing industry